2020
DOI: 10.1007/s12109-020-09732-2
|View full text |Cite
|
Sign up to set email alerts
|

Online Book Shopping in Vietnam: The Impact of the COVID-19 Pandemic Situation

Abstract: The coronavirus disease 2019 (COVID-19) pandemic will have a large impact on the publishing industry. This research aims to investigate the influences of the COVID-19 pandemic situation, utilitarian and hedonic motivations on consumer intention to buy books online. It conceptualizes the effects of the COVID-19 pandemic as situational influences, which involve the closure of physical bookstores, health risks associated with visiting such stores, online shopping trend and additional marketing efforts from online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 18 publications
8
67
0
4
Order By: Relevance
“…A study carried out by Hashem [130] claimed that the COVID-19 pandemic has escalated online shopping. In line with that, additionally, Nguyen et al [96] empirically found a significant impact of situational influence (COVID-19) on consumer behavior.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…A study carried out by Hashem [130] claimed that the COVID-19 pandemic has escalated online shopping. In line with that, additionally, Nguyen et al [96] empirically found a significant impact of situational influence (COVID-19) on consumer behavior.…”
Section: Discussionsupporting
confidence: 61%
“…OFDO service intentions had four statements adapted from [11,22]. Situational influences (COVID-19) were measured by five items adopted by Nguyen et al [96]. Similarly, items for OFDO service adoption were constructed by Akbar et al [78], and Yadav and Pathak [106].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Companies are recommended to understand the customers (Abena et al, 2020;Bastani & Bahrami, 2020;R. Y. Kim, 2020;Nguyen et al, 2020;Wang et al, 2020). In the current situation, it is recommended to market professionals to make digital content and interact with customers.…”
Section: Recommendations For Practitionersmentioning
confidence: 99%
“…Most of the researches used above mentioned methods and variables for the prediction of COVID-19 [ 39 41 ]. Multivariate evidence revealed that the epidemics condition with COVID-19 has an optimistic and important impact on online shopping [ 42 ]. Burstyn et al [ 43 ] have analysed clinical time series data besides SARS-CoV-2 epidemiologic illness to identify the common cause for COVID-19.…”
Section: Introductionmentioning
confidence: 99%